Mohebedine Al Khatib’s position on political and military issues in the arabian peninsula "1926-1948" - Mohammed Al-Sharif, Hussein (The Algerian Historical Journal, 2026)
After the end of the first world war in november 1918, by the truce signature between England with its allies and the Ottoman empire, the dream of the great arab country had evaporated because of England and France’s plans. The british soon implemented their colonial scheme of dividing the levant countries. Only the arabian peninsula with cutted edges came throgh this plan, where every prince retained what he seized of lands during the war. Cherif Hussein was a King on Hidjaz, Abdelaziz Ben Saoud a King of Nadjad. They got into a war between them because each of them wanted Alhidjaz for himself. Al Khatib was angry with the hashemites because they asked the British to support them in 1924. The Saoudians won the war and they constructed their country on islamic bases. Mohebedine Al Khatib was very impressed by this achievement and he consideled it an islamic victory and the best response to turkey laîc apostasy on islamic principles.